Analysis of the Gliding Pattern of the Canine Flexor Digitorum Profundus Tendon through the A2 Pulley - Uchiyama, Shigeharu (2008)
Friction between a tendon and its pulley was first quantified using the concept of the arc of contact. Studies of human tendons conformed closely to a theoretical nylon cable/nylon rod model. However, we observed differences in measured friction that depended on the direction of motion in the canine model. We hypothesized that fibrocartilaginous nodules in the tendon affected the measurements and attempted to develop a theoretical model to explain the observations we made. Two force transducers were connected to each end of the canine flexor digitorum profundus tendon and the forces were recorded when it was moved through the A2 pulley toward a direction of flexion by an actuator and then reversed a direction toward extension. The changes of a force as a function of tendon excursion were evaluated in 20 canine paws. A bead cable/rod model was developed to simulate the canine tendon-pulley complex. To interpret the results, a free body diagram was developed. The two prominent fibrocartilaginous nodules in the tendon were found to be responsible for deviation from a theoretical nylon-cable gliding around the rod model, in a fashion analogous to the effect of the patella on the quadriceps mechanism. A bead cable/rod model qualitatively reproduced the findings observed in the canine tendon-pulley complex. Frictional coefficient of the canine flexor tendon-pulley was 0.016±0.005. After accounting for the effect created by the geometry of two fibrocartilaginous nodules within the tendon, calculation of frictional force in the canine tendon was possible.